Raising Goats For Dummies, 2nd Edition - Smith, Cheryl K (Hoboken, NJ : John Wiley & Sons, Inc., 2021)
This fully updated guide provides in-depth information on this fun and profitable hobby. It introduces you to different breeds and leads you through choosing your goats, preparing the appropriate living space for them, selecting food, and understanding everything necessary to keep your goats happy and healthy
Keywords: Goats